ANALISIS KELAYAKAN USAHA PERIKANAN PURSE SEINE BERDASARKAN WILAYAH PENANGKAPAN DI PULAU AMBON - Rosihan Polhaupessy; W. Waileruny; D. Amura; Pirhel Pirhel (Universitas Pattimura, 2020)
Our research took place in several areas of Ambon Island to be able to represent fishing areas that operate around the waters of Ambon Island, including Latuhalat Village (South Ambon Island), Hitu Village (North Ambon Island), Waai Village (West Ambon Island) and Laha Village (Outside of Ambon Bay). So it is hoped that later it can provide a detailed description of the feasibility of purse seine fisheries business based on the fishing area on Ambon Island. A method of the survey to technique the sample in purposive sampling with total respondents was the owner of fisheries purse up seine 30 business unit. Analysis of the data used is the analysis of costs, revenues and business feasibility (NPV, Net B/C, Gross B/C and Paybeck Period). the results of the study can be concluded that the purse seine fishing business on Ambon Island provides quite high profits and this business is worth developing. The NPV of the business is positive, Net B/C, Gross B/C > 1 and the ability to return the investment that has been invested in the purse seine business on Ambon Island is an average time between 1.5 years to 2.7 years. Seen from the catching area, the Latuhalat location has a high Net B/C Ratio, Gross B/C Ratio and PP when compared to the other three Locations.